Dampak, Peluang, dan Tantangan Kebijakan Merger Bank Syariah terhadap Stabilitas Perekonomian Negara (Studi Kasus: Bank Syariah Indonesia) - Baharudin, Alden Rizky; Rasyidi, Alma Musa; Amrullah, M. Ridho Musfiq; Rahendro, Sabrina Wafa (Diponegoro Journal of Islamic Economics and Business, 2022)
This paper discusses policies carried out by the Indonesian government regarding to the merger of state-owned Islamic banks, namely BRI Syariah, BNI Syariah, and Bank Syariah Mandiri which were merged to form Bank Syariah Indonesia (BSI). The purpose of this paper is to analyze the impact, opportunities, and challenges of that merger on the stability of the country's economy. Results of this analysis will be useful not only for the Government of Indonesia but also for BSI in formulating strategies to develop opportunities and mitigate risks. The result of the analysis in this paper is that the policy of Islamic bank mergers is the right step for the Government of Indonesia to maintain the stability of the country's economy. This is because the merger of these three Islamic banks is able to increase the total assets and liabilities of Islamic banks so that the allocation of financing for MSME actors is even greater. Besides that, the merger of Islamic banks is considered to be able to expand market share penetration and can streamline company costs, such as capital expenditure, overhead costs, and so on. Another impact of the policy of the merger of state-owned Islamic banks is being able to compete nationally and internationally with conventional banks through the provision of more complete services, as well as being able to create healthy competition for the country's economy.